Contemporary approaches to the assessment of production functions (Journal of Economic Research & Business Administration, 2016)
Modeling of production functions and assessment of total factor pro-ductivity are the leading direction of current research.Modeling of pro-duction functions puts forward a number of questions the solution of which dependson the correctness of the results: which variables are used as output and production factors, the choice of the specification of the production function, at which level to conduct aggregation (the level of the industry, firm, region, etc.), which approaches apply to solve specific problems in the econometric estimation, which lead to the distortion of results (endogeneity in assessing factors, selection of firms in the sample, bias estimates et al.). Modern empirical research suggests different approaches to solving the problems of estimation of production functions. However, the unifying factor is the almost widespread use of panel dataduring the research